Behavioral barriers in the inclusion of neglected and underutilized species into mainstream diets - Atakan, Pelin; Günden, Cihat; Yercan, Murat; Mattas, Konstadinos; Knez, Marija (Frontiers in Sustainable Food Systems, 2025)
In recent years, there has been a notable trend toward a global demand for sustainable nutrition, coupled with increasing concerns regarding biodiversity. Consequently, this has prompted the reintroduction of underutilized and neglected species (NUS) into the agri-food market. NUS refers to previously cultivated species no longer grown due to economic, cultural, agronomic, or genetic factors. The primary reason for their neglect often lies in widespread agricultural practices such as monoculture and the intense competition inherent in the current global trade environment. These crops often embody cultural heritage and possess a diverse genetic profile specific to their region, thereby contributing to efforts aimed at preserving biodiversity. However, the revitalization of NUS faces various hindrances, including behavioral barriers that influence their inclusion into mainstream diets. This review aims to identify the behavioral factors that restrict or limit the inclusion of NUS in mainstream diets, utilizing the principles of the Prospect Theory. Peer-reviewed studies focusing on the consumer perspective of NUS were analyzed using an inductive approach. Given the limited number of studies conducted to date, the findings reveal a significant gap in our understanding of NUS consumption. As a practical contribution, we propose a design that reinterprets the MINDSPACE tool through the lens of the Fogg Behavioral Model, offering guidance for policy interventions and marketing strategies.